Exploring the influence of international governmental organisations on domestic child welfare policy and practice. (April 2013) - Axford, Nick
The influence of international governmental organisations (IGOs) on child welfare policy and practice in individual sovereign states is little explored. This article sets out the nature of these bodies' main work with children. It then considers the mechanisms through which they seek to influence national child welfare policy and practice and the extent to which they can make nation states comply. 'Soft' mechanisms, such as awareness-raising, compiling statistical data and demonstration projects are contrasted with 'hard' mechanisms, such as making law and financial intervention. The article then reviews the effects of this activity and the factors explaining the varied pattern. It concludes that child welfare policy and practice are increasingly subject to supranational influence and that this has important implications for those seeking to influence this field. 1